2009
DOI: 10.1007/s11998-009-9167-3
|View full text |Cite
|
Sign up to set email alerts
|

Drying and collapse of hollow latex

Abstract: Hollow latex particles are used as white pigments for paints and paper coatings. In the coating dispersion, each hollow particle is filled with water. As the coating dries, water vacates the latex, leaving an air-filled void sized to scatter light ($0.5 lm) within each particle. Examinations of dried coatings reveal that hollow particles can collapse, decreasing their light scattering efficiency. Cryogenic scanning electron microscopy (cryoSEM) was used to characterize the microstructure of coatings containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These include biomaterial applications such as drug delivery, 1 gene delivery, 2 artificial cells 3,4 and regenerative medicine. 5 They also have application in surface coatings, 6 catalysis, 7 light weight fillers, encapsulation of cosmetics and vessels for confined reactions. 3,8 The introduction of environmental response enhances application opportunities, especially in the context of biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…These include biomaterial applications such as drug delivery, 1 gene delivery, 2 artificial cells 3,4 and regenerative medicine. 5 They also have application in surface coatings, 6 catalysis, 7 light weight fillers, encapsulation of cosmetics and vessels for confined reactions. 3,8 The introduction of environmental response enhances application opportunities, especially in the context of biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration distributions in the thickness direction have been successfully measured by confocal micro Raman spectroscopy (RMS), Infrared microscopy (IRM), and Magnetic resonance (MR), and summarized by using non-dimensional numbers of Pe and Ns. Despite the formidable consistency with the computational results for hard particle-solvent and polymer-solvent systems, the spatial resolutions of these techniques are currently not sufficient to elucidate the detailed dr ying kinetics in suspensions of deformable particles 23)- 25) , those containing surfactants 20), 31) , suspensions on a moving substrate Fig. 6 Variations in surfactant distribution in shrinking suspension film 31) .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrar y, no preferential segregation of smaller particles has been obser ved for a bimodal aqueous suspension containing hollow polystyrene latex of 0.5 mm in diameter and polyvynil acetate latex of 0.1 mm in diameter 25) . CryoSEM observations revealed that hollow PS particles showed a homogeneous distribution across the film, and surrounded by smaller particles coalescing each other.…”
Section: Bimodal Soft Particle-solvent Systemmentioning
confidence: 94%
“…[20][21][22][23] For obtaining opaque coatings at ambient condition, hollow latexes must be applied together with other film-forming resins, hinders, or coalescents. 24,25 In this work, based on the osmotic swelling method and the previous research on the three-layer core/shell latex, 18,19 a four-layer core/ shell polymer latex with an outermost soft film-forming layer was designed to prepare the hollow latex with both opaque and self film-forming properties, and effects of the BA/St mass ratio, DVB content, and the core/film-forming layer mass ratio in the film-forming layer preparation on the four-layer core/shell latex and the final hollow latex were investigated.…”
Section: Introductionmentioning
confidence: 99%